ECOLOGICAL ASPECTS OF INFLUENCE OF SOLID DOMESTIC WASTES ON THE ENVIRONMENT. FILTRATE - Самойлік, М. С.; Молчанова, А. В. (Scientific Progress & Innovations, 2018)
An increasing number of industrial and food products for the population, respectively, solid waste increases. Nature has no mechanisms of recycling and disposal of waste produced by society, because of it waste accumulate in the biosphere. The problem of waste is currently one of the major environmental problems. The problem of waste is a key environmental issues. Landfill – an example of human activities, pollution of soil, surface water, soil and undergroundwater.